Management of Teacher Performance Improvement at Madrasah Tsanawiyah Negeri 2 Padangsidimpuan City - Amiruddin MS; Ummi Kalsum; Dina Nadira Amelia Siahaan (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2022)
This study's overarching goal is to describe the administration of teacher performance enhancement. The precise goals are to explain: 1) planning for increasing teacher performance, 2) putting the program into practice, and 3) assessing the management of teacher performance improvement. Interviews, observations, and documentation are used as data gathering methods in this descriptive qualitative research design. Teachers and principals served as the research participants. The outcomes demonstrated that management of increasing teacher performance through planning and evaluation was successful. However, several issues, including both internal and external issues, were discovered as a result of the management of increasing teacher performance.